2002
DOI: 10.1590/s1516-35982002000500001
|View full text |Cite
|
Sign up to set email alerts
|

Composição corporal de tambaqui, Colossoma macropomum, e matrinxã, Brycon cephalus, em sistemas de cultivo intensivo, em igarapé, e semi-intensivo, em viveiros

Abstract: RESUMO -Foi conduzido um estudo para avaliar o efeito do sistema de cultivo na composição corporal de juvenis de tambaqui e matrinxã, quando cultivados em sistema intensivo, em canal de igarapé, e em sistema semi-intensivo, em viveiros. Foram usados juvenis de tambaqui e matrinxã com comprimento e peso médio inicial de 15,4 cm e 88,3 g e 23,4 cm e 219,4 g, respectivamente. Os juvenis de cada espécie foram estocados a uma densidade de 10 e 1 peixe/m 3 no sistema intensivo e semi-intensivo, respectivamente. O pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
4
19

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 10 publications
(10 reference statements)
2
22
4
19
Order By: Relevance
“…Arbeláez- Rojas et al (2002) and Izel and Melo (2004) reported lower daily weight gain rates for the tambaqui, or rather, there was a gain of up to 4.5 g/day after 170 days and 1.69 g/day after 240 days, respectively. Breeding program families registered gains over 29.0% when compared to those in current assay, and in less time, emphasizing the importance of breeding program for tambaqui.…”
Section: Resultsmentioning
confidence: 95%
“…Arbeláez- Rojas et al (2002) and Izel and Melo (2004) reported lower daily weight gain rates for the tambaqui, or rather, there was a gain of up to 4.5 g/day after 170 days and 1.69 g/day after 240 days, respectively. Breeding program families registered gains over 29.0% when compared to those in current assay, and in less time, emphasizing the importance of breeding program for tambaqui.…”
Section: Resultsmentioning
confidence: 95%
“…Provavelmente, tais características tornam este produto de maior aceitação no mercado consumidor, assim como mais atraentes para produtores e indústrias. Dessa forma, a oferta de um produto com baixo teor de gordura aumenta o rendimento de carcaça no processamento, assim como melhora a qualidade do produto final 26 , aumentando o prazo de validade do pescado devido à menor disponibilidade de ácidos graxos insaturados disponíveis para o processo de peroxidação lipídica.…”
Section: Resultsunclassified
“…Tambaqui (Colossoma macropomum) and matrinxã (Brycon amazonicus) are fish species native to the Amazon region that are produced in semi-intensive aquaculture and are important economic alternatives in northern Brazil (Arbeláez-Rojas et al 2002, Sebrae 2015. Tambaqui is the main native fish farmed in Brazil, for its meat of high quality and good taste.…”
Section: Introductionmentioning
confidence: 99%